Teatro da encarnação: contribuições do Teatro de Animação para a Teoloda Missão - Saldanha, Marcelo Ramos (2012)
This dissertation presents an introduction to the theorization on the Incarna- tion Theater, an artistic and missionary practice developed by the author in his pasto- ral labor, and its relation with the theology of Integral Mission. Under the notion of a double incarnation by the puppet, the Incarnation Theater is a bodily manifestation of children's ludic or playful behavior, where the adult and the child become beings who dialogue in a space of shared meanings. As this incarnated theater is a missionary appropriation of animated theater, and as an artistic manifestation has great similari- ties with the act of playing, we will approach it initially as a technique, speaking of the actor, the puppet and the child, starting from the encounter of the concrete world of the adult with the ludic-syncretic one of the child. After, starting from the Philosophy of Life of Michael Henry and the Integral Mission theology, we will approach it as a powerful means of apprehension of knowledges of life itself, which, in its self-giving to us, builds a symbolic universe rich in experiences, where both adult and child can see themselves as life-borne, in a kenotic space of multiple possibilities of interaction and transformation.